Proses Pemodelan Saintifik pada Miskonsepsi Mekanika Kuantum - Hermawan, Dian Wahid (Jurnal Tarbiyah : Jurnal Ilmiah Kependidikan, 2018)
The process of misconceptions about the concepts of quantum physics in students needs to be comprehensively analyzed. This is because most of the revision process of student misconception is done directly by simply replacing the wrong explanation with the correct explanation. While to understand the theory and hypothesis of quantum physics phenomena requires abstract physics model and formal mathematical language. Modeling done by the mind sometimes does not require image image in the brain. As between the wave function and the particle position associated with the mathematical model. The misconceptions in quantum physics occur because of the wrong scientific conceptual modeling process. The scientific conceptual model is divided into four dimensions: domain, composition, structure and organization. Analysis of the misconception process modeling using these dimensions will be done on the phenomenon of quantum physics. The misunderstanding of the definition of the wave function concept Ñ° (x) occurs due to the incorrect dimensions of the models interactive structure. While the misconception of the concept of quantity of energy and the relationship of wave function with probability, occurs in the dimension of the behavioral structure of the model. In the concept of position measurement and momentum of quantum systems, errors occur in both structures.